2021
DOI: 10.1111/eip.13189
|View full text |Cite
|
Sign up to set email alerts
|

Young people's attitudes towards integrating physical activity as part of mental health treatment: A cross‐sectional study in youth mental health services

Abstract: Introduction Due to the significant burden associated with mental disorders that have their onset in youth, there is a critical need to improve treatments and treatment outcomes. Given the evidence for physical activity (PA) as an effective intervention for reducing depression and anxiety symptoms in young people, we examined young people's attitudes towards and acceptability of PA as part of mental health treatment, predictors of current engagement in PA and predictors of attitudes towards PA as a treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…One study indicated youth with ADHD were less likely to play sports, which may contribute to lower physical activity levels [ 28 ]. A survey of teens and young adults receiving mental health services indicated interest in physical activity promotion being offered in conjunction with mental health services [ 29 ]. However, interest in physical activity was inversely related to the participant’s perception of exercise benefits and self-rated autonomy toward exercising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated youth with ADHD were less likely to play sports, which may contribute to lower physical activity levels [ 28 ]. A survey of teens and young adults receiving mental health services indicated interest in physical activity promotion being offered in conjunction with mental health services [ 29 ]. However, interest in physical activity was inversely related to the participant’s perception of exercise benefits and self-rated autonomy toward exercising.…”
Section: Discussionmentioning
confidence: 99%
“…However, interest in physical activity was inversely related to the participant’s perception of exercise benefits and self-rated autonomy toward exercising. Parker et al suggested the use of a collaborative problem-solving process to promote physical activity among young people using mental health services [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in regular physical activity (PA) has numerous health benefits such as reducing the risk of hypertension, cardiovascular diseases, anxiety, and depression (Hallal et al, 2012, Parker et al, 2021, Guo and Zhang, 2022, Liu et al, 2022, Jakicic et al, 2022, Howell and Booth, 2022. However, large proportions of the population in many developed and developing countries across the globe are leading inactive lifestyle (Hallal et al, 2012, Teo andRafiq, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This enhanced acceptance of experiences is thought to lead to increased distress tolerance (Carpenter et al, 2019). Therefore, mindfulness could be associated with reduced perceived barriers to exercise engagement, through greater acceptance of negative or uncomfortable thoughts or sensations related to exercise engagement, such as low mood, fatigue or feeling self‐conscious (Firth et al, 2016); (Parker et al, 2021). Thus, the current study aimed to examine the relationship between mindfulness, psychological distress and physical activity outcomes in help‐seeking young Australians.…”
Section: Introductionmentioning
confidence: 99%
“…Future work should explore the relationship between mindfulness, perceived barriers and other relevant factors that impact levels of exercise engagement. As young people hold positive views of the potential of physical activity as part of mental health treatment(Parker et al, 2021) future studies may examine integrating mindfulness approaches to exercise engagement within psychological treatment.4.1 | ConclusionDispositional mindfulness may reduce perceived barriers to exercise engagement in help-seeking young people, however future studies should also account for other factors that influence exercise engagement levels.ACKNOWLEDGEMENTWe gratefully acknowledge the clinical and management staff of headspace Sunshine, Glenroy, Werribee and Craigieburn for supporting the project. Portions of the data collected in this project was included in an Honours of Psychology thesis by ET, supervised by AGP and MP.…”
mentioning
confidence: 99%